THE ARCHETYPE ANALYSIS OF MAIN CHARACTER IN HUSH, HUSH NOVEL - Nurdayanti, Chevie; Natsir, M.; Lubis, Indah Sari (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
Hush, Hush was a young adult fantasy novel written by Becca Fitzpatrick which told the journey of Fallen Angel named Patch. There were two problems of study, they were: what forms of archetype are appeared in Patch’s personality and how is the main character  described in Hush, Hush novel. The purposes of this study were decribed the archetype forms are appeared in Patch Personality and describes the main character personality in Hush, Hush novel. Qualitative Reseach was used to interpretating all phenomena’s and issues related Patch personality. The researcher applied this research as literaty criticism since the researcher was the key intruments it self  in analysis and interpretation on literary work. Carl Jung Gustav theory about archetype was used as the main theory to describe and analyze the main character. The data of this study were collected from Hush, Hush novel by Becca Fitzpatrick. The result of this study showed six forms of archetype were appeared in main character’s personality, there were the persona, the shadow, the anima and animus, the great mother, the wise old man and the self and two characters personality of main character, such as myterious and ambitious.